Construction and Characterization of Novel Hirulog Variants with Antithrombin and Antiplatelet Activities - Yu, Zheng; Huang, Yuanyuan; Wang, Yu; Dai, Chen; Dong, Mingxin; Liu, Zhuguo; Yu, Shuo; Hu, Jie; Dai, Qiuyun (Protein and Peptide Letters, 2014)
The RGD sequence was used to design potent hirudin isoform 3 mimetic peptides with both antithrombin activity and antiplatelet aggregation activity. The RGD and proline were inserted between the catalytic active binding domain (D-Phe-Pro-Arg-Pro) on the N-terminus and the anion-binding exosite binding domain (QGDFEPIPEDAYDE) on the Cterminus. Thrombin titration assay and ATP-induced platelet aggregation test revealed that the peptide with the linker RGDWP or RGDGP possessed potent antithrombin and antiplatelet activities, while other peptides without the Pro residue in the linker only showed antithrombin activity. Similar results were obtained in the RGD-containing hirulog-1 variants. Our study indicates that the inserted Pro residue facilitates the exposure of RGD and the binding of the peptide to glycoprotein IIb/IIIa (GPIIb/IIIa). The strategy of combining the RGD sequence and the Pro residue may be used for future designs of bifunctional antithrombotic agents.
Keywords: RGD-motif